2023
DOI: 10.1128/spectrum.04938-22
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Bombyx mori Cytoplasmic Polyhedrosis Virus NSP8 and BmAgo2 Inhibits RNA Interference and Enhances Virus Proliferation

Abstract: It has been reported that the RNAi pathway is inhibited by binding RNAi suppressors encoded by some insect-specific viruses belonging to Dicistroviridae , Nodaviridae , or Birnaviridae to dsRNAs to protect dsRNAs from being cut by Dicer-2. However, it is unknown whether BmCPV, belonging to Spinareoviridae , encodes an RNAi suppressor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…It is not known whether these functions are carried out by the N-terminal SPD-like domain of p44, by its central linker (predicted disordered), or by its C-terminal WIV domain (). The same study found that p44 coprecipitated the genomic dsRNA of cypovirus 1, suggesting that p44 binds genomic dsRNA [67]. However, earlier studies reported that p44 bound ssRNA but not dsRNA, through its central linker [68].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not known whether these functions are carried out by the N-terminal SPD-like domain of p44, by its central linker (predicted disordered), or by its C-terminal WIV domain (). The same study found that p44 coprecipitated the genomic dsRNA of cypovirus 1, suggesting that p44 binds genomic dsRNA [67]. However, earlier studies reported that p44 bound ssRNA but not dsRNA, through its central linker [68].…”
Section: Resultsmentioning
confidence: 99%
“…2d). The same study found that p44 coprecipitated the genomic dsRNA of cypovirus 1, suggesting that p44 binds genomic dsRNA [67]. However, earlier studies reported that p44 bound ssRNA but not dsRNA, through its central linker [68].…”
Section: Wiv Is Probably a Virulence Factor That Facilitates Infectio...mentioning
confidence: 91%
See 1 more Smart Citation